Customer participation in knowledge intensive business services: Perceived value outcomes from a dyadic perspective - Mekhail Mustak (Elsevier, 2022)
Knowledge intensive business services (KIBS) are considered a cornerstone of contemporary developed economies. Successful production and delivery of these services, and thus their perceived value outcomes, highly depend on customer participation (CP) in the service processes. However, the extant understanding of the perceived value outcomes of CP, which is crucial to the appropriate inducement and integration of organizational resources in service processes, is limited. Through the exploratory investigation of three dyadic cases, each comprising one customer and one service provider organization engaged in a knowledge-based service project, this study addressed this crucial topic. Results indicated four categories of perceived value outcomes emerged through CP: functional, economic, relational, and strategic values. The study provides insights on the evolution of value perceptions over time, the individual value components within each value category, and perceptual similarities and differences between customer and provider organizations. Further, these results indicate that various value outcomes of CP receive divergent levels of attention from personnel in different organizational hierarchies. The paper provides useful and applicable suggestions for managers, especially in the context of technology-based KIBS and solutions.